The impact of food structure on taste and digestibility. Issue 10 (18th May 2016) - Lillford, P. J.
Abstract : The current knowledge on how food structures relate to perception is discussed. Abstract : The modern food chain depends on complex interactions between businesses from farming to retail. Until recently their success depended upon providing consumers with safe, convenient food which was pleasant to eat, at a reasonable value for money. This has required detailed research into how food structures deliver recognisable and preferred types of foods, from hard solids to thick liquids. Fortunately the consumer is able to detect and report sensations of texture and flavour which can be related to the composition, structure and breakdown of food in the mouth. Chemists, physicists and engineers can attempt to build mechanistic models of how structures relate to perception. The state of the art in our understanding and design capabilities are reviewed. In the developed world, the success is self evident as food prices (as a proportion of income) have decreased and there is a surfeit of choice on the supermarket shelf. More recently, the requirement to add a balanced healthy diet to the simple pleasure of eating has become the new target. This is a different type of challenge. The effects of diet on health are long term, and not easily reported by the consumer. Whilst we know something of how the digestive tract works in breaking down foods, we know little of how food structure impacts upon this process, and even less of how the neural and metabolic feedback systems operate to relate food structures to satiety and satiation. Therefore, in the absence of causal models relating structures to eating habits, structures designed to achieve both immediate pleasure and long term healthy eating are much more speculative. What we think we know, and what we need to know are reviewed. There is no doubt that other skills, in nutrition, physiology, neuroscience, and molecular biology etc . will need to be added to the classical approaches of food materials science and engineering if these challenges are to be met.